Walking on eggshells - Dóra S. Bjarnason (Educare)
This article takes up some of the ethical issues at stake when qualitative inquiry involves people in vulnerable situations, such as the young, the very old, the sick or disabled or minority groups – people, in short, who are often labelled as “the other”. Ethical issues and dilemmas appear at every juncture of the research process and also when the researcher decides what to publish and why. The article starts with some of the issues and experiences the author brings to the table after working in the field of inclusive education and disability research for over three decades. Next it offers some notes on qualitative inquiry and then it moves on to explore the ethics, ethical issues and dilemmas inevitably part and parcel of all such inquiry. Then it applies examples from the author’s fieldwork to the discussion of ethical issues and dilemmas in qualitative encountered in qualitative research with people in vulnerable situations. Examples are in particular drawn from the authors recent study that involved interviews with Icelandic parents of disabled children. The ethical issues and dilemmas touched upon include those related to gaining access, the interview situation itself, including the building of rapport and the fine line between gathering the data, data analysis, ethical issues related to what to select from privileged knowledge, and other things that concern the writing up of sensitive data. Finally, some thought is given to publications, their interpretations by the reader and their use or abuse.